What Was the Survival of Megaprostheses in Lower Limb Reconstructions After Tumor Resections?. Issue 3 (March 2015) - Capanna, Rodolfo; Scoccianti, Guido; Frenos, Filippo; Vilardi, Antonio; Beltrami, Giovanni; Campanacci, Domenico Andrea
Abstract: Background: Prosthetic replacement is the most commonly used option for reconstruction of osteoarticular bone loss resulting from bone neoplasm resection or prosthetic failure. Starting in late 2001, we began exclusively using a single system for large‐segment osteoarticular reconstruction after tumor resection; to our knowledge, there are no published series from one center evaluating the use of this implant. Questions/purposes: We investigated the following issues: (1) What is the overall survival, excluding local tumor recurrence, for these endoprostheses used for tumor reconstructions of the lower extremities (knee and hip)? (2) What types of failure were observed in these reconstructions? (3) Do the survival and complications vary according to site of implant? Methods: Between September 2001 and March 2012, we exclusively used this implant for tumor reconstructions. During that time, 278 patients underwent tumor reconstructions of the hip or knee, of whom 200 (72%) were available at a minimum 2 years followup. Seventy‐eight patients were excluded from the study for insufficient followup as a result of early death (42) or loss at followup (36). The reconstruction types were the following: proximal femur (69 cases), distal femur (87), proximal tibia (32), and total knee (12). Failures were classified according to the Henderson classification. Nine patients among those with followup shorter than 2 years had presented one or more failures and they were included in our analysis but separately evaluated. Results: Overall survival (no further surgical procedures of any type after primary surgery), excluding Type 5 failure (tumor recurrence), was 75.9% at 5 years and 66.2% at 10 years. Seventy‐one failures occurred in 58 implants (29%). Mechanical failures accounted for 59.2% and nonmechanical failures for 40.8%. The first causes of failure of the implants were the result of soft tissue failure in 6%, aseptic loosening in 3%, structural failure in 7%, infection in 8.5%, and tumor recurrence in 4.5% of the whole series. Nine implants sustained two or more failures. Overall incidence of infection was 9.5%. No statistically significant differences were observed according to anatomical site. Conclusions: Like in the case with many such complex oncologic reconstructions, the failure rate at short‐ to midterm in this group was over 20%. Comparative trials are called for to ascertain whether one implant is superior to another. Infection and structural failure were the most frequent modes of failure in our experience. Level of Evidence: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.